CARTOON STORY MAKER AS THE DEVELOPED LEARNING MEDIA IN WRITING DESCRIPTIVE TEXT FOR JUNIOR HIGHSCHOOL STUDENTS - Aryokta Ismawan; Anni Holila Pulungan; Nora Ronita Dewi (Universitas Negeri Medan, 2018)
The aim of this study was to develop learning media in Writing Descriptive Text for Grade VIII of Junior Highschool Students. This study was conducted by using Research and Development (R&D) design through six stages; gathering information and data, analyzing data, designing materials, validating by experts, revising, and final product.. The subject of the study was Grade VIII of SMP N 3 LubukPakam. The data were gathered by administering interview to English teacher and distributing questionnaire to 30 respondents to get the students’ needs. The interview and questionnaire results prove that the students needs English learning media which can motivate the students to understand about the descriptive writing. The product has been validated by experts. The result of the product was videos that contain audio-visual media to be used in mastering the descriptive text writing. Keywords: Cartoon Story Maker, Descriptive Text, Research and Development (R&D)